Impact of Firm Heterogeneity on Direct and Spillover Effects of FDI: Micro Evidence from Ten Transition Countries - Jože P. Damijan; Matija Rojec; Boris Majcen; Mark Knell (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
This paper presents a comparative study of the importance of direct technology transfer and spillovers through FDI on a set of ten transition countries, using a common methodology and appropriate methods to account for selection and simultaneity correction. This paper considers by far the largest firm level dataset (more than 90,000 firms) used by any study on the spillover effects of FDI. The main novelty of the paper is the explicit control for various sources of firm heterogeneity when accounting for different effects of FDI on firm perfirmance. Controlling for these variables leads to some interesting results which contrast with the previous empirical work in the field. We find that horizontal spillovers have become increasingly important over the last decade, and they may even become more important than vertical spillovers. Furthfirmore, this work shows that the heterogeneity of firms in tfirms of absorptive capacity, size, productivity and technology levels affect the results. These findings suggest that both direct effects from foreign ownership as well as the spillovers from foreign firms substantially depend on the absorptive capacity and productivity level of individual firms. Only more productive firms and firms with higher absorptive capacities are able to both compete with foreign affiliates in the same sector and benefit from the increased upstream demand for intfirmediates generated by foreign affiliates. In addition, these results show that foreign presence may also affect smaller firms to a larger extent than larger firms, but this impact may be in either direction.
Keywords: D24; F14; 330; Foreign direct investment; technology transfer; spillovers; transition economies; firm heterogeneity; Direktinvestition; Technologietransfer; Spillover-Effekt; Schätzung; Osteuropa